SMART CANARY BASED ON IOT WITH RFID AND TELEGRAM - Rillya Arundaa; Wisard Widsli Kalengkongan (Jurnal Teknologi dan Sistem Tertanam, 2022)
Today many people are fond of raising birds, ranging from small cages to large-scale cages. One of the kind of bird is canary. Where these canaries will be given food and drink every seven in the morning. An idea emerged to make this research entitled Smart Canary Bird Cage Based Internet Of Things With Rfid And Telegram. This research has also been able to produce a tool or system that monitors feed and automatically fills and conditions the cage at any time using a smartphone. The workings of the ultrasonic system that is above the drinking place will detect the drinking distance if you have finished drinking it will fill it automatically. The same way for the loadcell will be under the feed and under the cage to detect the weight of the feed and the weight of the manure if the feed runs out then the feed will fill automatically, for the DHT11 temperature the sensor will detect the temperature if the temperature is below the standard temperature then the light will turn on if the temperature is above then the fan will turn on. All conditions in the cage will automatically be entered into the database so that they can be displayed via a smartphone. It is hoped that with this tool, the owner of the cage will be given convenience so that they are not required to enter the cage to find out the condition of the cage, feed and birds. Based on the several reasons above and developing previous research, the author suggests creating a system or tool entitled “Internet Of Things-Based Smart Canary Cages With Rfid And Telegram". This research was conducted with the aim of preventing people who raise birds from getting sick easily and providing comfort for bird owners when they are not around the cage. This tool or system is able to provide notifications to telegrams when the bird's cage is about to be stolen, provide food and drink for the birds. automatically according to the needs of the birds and carried out regularly.